DEVELOPING STUDENTS' SKILLS AND SKILLS TO WORK ON RELIEF SHAPES IN SCULPTURE CLASSES - Kadyrov Bobir Bakhtiyorovich (American Journals Publishing, 2022)
This article talks about the types of teaching of sculpture in school conditions, the function and content of sculpture, and the types of small sculpture.
Keywords: sculpture and monuments, compositions, pencil drawing, three dimensions, relief images, animalistics